2015
DOI: 10.1614/ipsm-d-14-00042.1
|View full text |Cite
|
Sign up to set email alerts
|

Propagule Pressure and Disturbance Drive the Invasion of Perennial False-Brome (Brachypodium sylvaticum)

Abstract: An ecosystem's invasibility is influenced by changes in biotic and abiotic resistances, which often occur due to shifts in the prevailing disturbance regime. The susceptibility of a community to intrusion by nonnative species may interact with propagule pressure to determine the extent of a biological invasion. We examined how propagule pressure, forest community structure, and disturbance interact to influence the invasibility of temperate Pacific Northwest forests by the newly invasive grass, perennial false… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…). Our findings parallel the negative relationship between disturbance and the abundance and cover of native species that is typically found by studies of non‐native invasion of natural ecosystems (Lake & Leishman ; Taylor & Cruzan ). However, our study was the first to quantify this relationship for native species in novel habitats.…”
Section: Discussionsupporting
confidence: 88%
“…). Our findings parallel the negative relationship between disturbance and the abundance and cover of native species that is typically found by studies of non‐native invasion of natural ecosystems (Lake & Leishman ; Taylor & Cruzan ). However, our study was the first to quantify this relationship for native species in novel habitats.…”
Section: Discussionsupporting
confidence: 88%
“…Seeds of Brachypodium sylvaticum and its native competitor Bromus vulgaris were collected from several sites within Milo McIver State Park, Estacada, Oregon. Within Milo McIver, B. sylvaticum is distributed along elevational, moisture, and light gradients (Taylor and Cruzan, 2015) ranging from dry or drier upland, coniferous forests to riparian habitats and deciduous, lowland forests. The native competitor B. vulgaris was chosen due to its similar environmental preference and proximity to B. sylvaticum within the majority of sites sampled.…”
Section: Methodsmentioning
confidence: 99%
“…Slender false brome is ideal for use in this study because its performance and competitive ability has been found to be influenced by mycorrhizal colonization (C. Lee, Portland State University, personal communication; R. Workman, unpublished data). It is also ideal for use in examining invasive infilling processes—the potential for the invasive to invade intact native plant communities—not the likelihood of primary invasion success or how the exotic plant might establish in a new environment (Taylor and Cruzan, 2015; Taylor et al, 2015). Understanding the potential roles of CMN and root interactions on competitive outcomes is important for predicting the infilling success and impacts of B. sylvaticum on native plant communities.…”
mentioning
confidence: 99%
“…In native regions, plants can become infected with an endophytic fungus which inhibits seedling survival (Roy et al ., ), while the infectious endophyte does not occur in invasive regions. Additionally, B. sylvaticum invasion is associated with sites that have a recent history of physical disturbances, such as logging, that aid primary colonization (Taylor & Cruzan, ). Moreover, several mechanisms have been found to reduce the effects of bottlenecks in the invasive region for B. sylvaticum .…”
Section: Discussionmentioning
confidence: 99%